High-energy phonon branches of an individual metallic carbon nanotube - Maultzsch, Janina; et al. (Physical Review Letters, 2003)
We present excitation-energy dependent Raman measurements between 2.05 and 2.41 eV on the same individual carbon nanotube. We find a change in the Raman frequencies of both the D mode (63 cm(-1)/eV) and the high-energy modes. The observed frequencies of the modes at approximate to1600 cm(-1) as a function of laser-energy map the phonon dispersion relation of a metallic tube near the Gamma point of the Brillouin zone. Our results prove the entire first-order Raman spectrum in single-wall carbon nanotubes to originate from double-resonant scattering. Moreover, we confirm experimentally the phonon softening in metallic tubes by a Peierls-like mechanism.